HCV Induces Telomerase Reverse Transcriptase, Increases Its Catalytic Activity, and Promotes Caspase Degradation in Infected Human Hepatocytes. - Zhaowen Zhu; Huy Tran; M Meleah Mathahs; Thomas O Moninger; Warren N Schmidt (PLoS ONE)
Introduction Telomerase repairs the telomeric ends of chromosomes and is active in nearly all malignant cells. Hepatitis C virus (HCV) is known to be oncogenic and potential interactions with the telomerase system require further study. We determined the effects of HCV infection on human telomerase reverse transcriptase (TERT) expression and enzyme activity in primary human hepatocytes and continuous cell lines. Results Primary human hepatocytes and Huh-7.5 hepatoma cells showed early de novo TERT protein expression 2-4 days after infection and these events coincided with increased TERT promoter activation, TERT mRNA, and telomerase activity. Immunoprecipitation studies demonstrated that NS3-4A protease-helicase, in contrast to core or NS5A, specifically bound to the C-terminal region of TERT through interactions between helicase domain 2 and protease sequences. Increased telomerase activity was noted when NS3-4A was transfected into cells, when added to reconstituted mixtures of TERT and telomerase RNA, and when incubated with high molecular weight telomerase 'holoenzyme' complexes. The NS3-4A catalytic effect on telomerase was inhibited with primuline or danoprevir, agents that are known to inhibit NS3 helicase and protease activities respectively. In HCV infected cells, NS3-4A could be specifically recovered with telomerase holoenzyme complexes in contrast to NS5A or core protein. HCV infection also activated the effector caspase 7 which is known to target TERT. Activation coincided with the appearance of lower molecular weight carboxy-terminal fragment(s) of TERT, chiefly sized at 45 kD, which could be inhibited with pancaspase or caspase 7 inhibitors. Conclusions HCV infection induces TERT expression and stimulates telomerase activity in addition to triggering Caspase activity that leads to increased TERT degradation. These activities suggest multiple points whereby the virus can influence neoplasia. The NS3-4A protease-helicase can directly bind to TERT, increase telomerase activity, and thus potentially influence telomere repair and host cell neoplastic behavior.